การพัฒนาเซรามิกเมมเบรนชนิดอลูมินาระดับไมโครแบบท่อกลวงเพื่อการทำน้ำยางสดให้เข้มข้น - ดรุณี ผ่องสุวรรณ (มหาวิทยาลัยสงขลานครินทร์, 2012)
Ceramic membranes were prepared from alumina combined with additive bentonite and calcium carbonate. The mixture compositions were selected by adjusting raw material of alumina: bentonite and calcium carbonate of 89-99 g : 1-7 g : 2-6 g per 100 g, respectively. The plaster was then slipped casting to obtain a tubular shape membrane. The tube length was 200 mm with diameter of 17 mm and thickness 3 mm. The reaction sintering temperature of potous alumina membrane was realized From 1100-1300°C with a rate of 3 °C/min. The results showed that the firing temperature of 1200 °C and the mixtures composition coded 7B (alumina 93% and bentonite 79%) and coded 4CCSB (alumina 91% bentonite 5% and calcium carbonate 4% ) are the best firing temperature and composition for making porous ceramic. The highest porosities of the product ceramic membrane were 48-50 % with average pore sizes of 0.7-0.8 um whereas the linear shrinkage, the water absorption and the bending strength were about 1.2 - 1.9 %, 37 - 39 % and 18 - 19 MPa respectively. The water pernmeability of membrane 7B and 4CC5B prepared at 1200 °C were 813 and 754 L/m h respectively at pressure 20 psi. Filtrations of natural rubber latex at 5%, 15% and 30% concentration are performed at pressure 80 psi using membrane 7B and membrane ICCSB pro-conditioned by dipping in 10% SDS. The perreate flux and rejection TSC at those three concentrations for membrane 7B are 12.11, 1.75 and 1.52 L.m' h'and 86%, 84% and 87%, respectively, and 10.23, 1.25 and 102 L.m" h' and 86%, 86% and 84%, respectively, for membrane 4CCSB. The mean particle diameters analyzed by laser particle size analysis of feed solution of clear serum and permeate solution using a cross-flow MF with membrane 4CCSB at pressure 60 psi were 1.201 and 0.4-0.2 um